Punctuation for Now - McDermott, J. author. aut Link
XIX, 213 p.
Keywords: It's or Its? Full stop inside or outside the inverted commas? What's the difference between a semi-colon and a colon? Cooperate or co-operate? Punctuation For Now describes in a witty but authoritative way how our present system of punctuation has grown out of the history of our language. It also indicates the conventions that govern the best punctuation in the English of today. The rules are set out clearly, and reinforced by abundant examples from the work of such authors as Kingsley Amis and Evelyn Waugh. Anyone with an examination to pass, or with a child who is learning to use English, or who writes it for a living, will find Punctuation For Now an invaluable guide and friend.